Pathogen‐Mimicking Polymeric Nanoparticles based on Dopamine Polymerization as Vaccines Adjuvants Induce Robust Humoral and Cellular Immune Responses. Issue 13 (5th February 2016) - Liu, Qi; Jia, Jilei; Yang, Tingyuan; Fan, Qingze; Wang, Lianyan; Ma, Guanghui
Abstract : Aiming to enhance the immunogenicity of subunit vaccines, a novel antigen delivery and adjuvant system based on dopamine polymerization on the surface of poly(d, l ‐lactic‐glycolic‐acid) nanoparticles (NPs) with multiple mechanisms of immunity enhancement is developed. The mussel‐inspired biomimetic polydopamine (pD) not only serves as a coating to NPs but also functionalizes NP surfaces. The method is facile and mild including simple incubation of the preformed NPs in the weak alkaline dopamine solution, and incorporation of hepatitis B surface antigen and TLR9 agonist unmethylated cytosine‐guanine (CpG) motif with the pD surface. The as‐constructed NPs possess pathogen‐mimicking manners owing to their size, shape, and surface molecular immune‐activating properties given by CpG. The biocompatibility and biosafety of these pathogen‐mimicking NPs are confirmed using bone marrow‐derived dendritic cells. Pathogen‐mimicking NPs hold great potential as vaccine delivery and adjuvant system due to their ability to: 1) enhance cytokine secretion and immune cell recruitment at the injection site; 2) significantly activate and maturate dendritic cells; 3) induce stronger humoral and cellular immune responses in vivo. Furthermore, this simple and versatile dopamine polymerization method can be applicable to endow NPs with characteristics to mimic pathogen structure and function, and manipulate NPs for the generation of efficacious vaccine adjuvants. Abstract : Pathogen‐mimicking nanoparticles (NPs) as vaccine adjuvant and delivery systems are constructed based on facile dopamine polymerization with antigen and immune‐activating unmethylated cytosine‐guanidine motifs on the surface of poly(d, l ‐lactic‐glycolic‐acid) NPs. These NPs with excellent biocompatibility and biosafety enhance the effect in evoking innate immunity and eliciting effective antibody and T cell responses.